Factors Influencing Northern Bobwhite Hunter Success on a Public Wildlife Management Area in Kentucky - Jarred M. Brooke; John J. Morgan; Danna L. Baxley; Craig Harper; Pat Keyser (National Quail Symposium Proceedings, 2017)
Hunter success is a critical measure of northern bobwhite (Colinus virginianus) restoration. Understanding the factors influencing hunter success can guide wildlife agencies in efforts to improve success and satisfaction and sustain hunter support of conservation initiatives. We compared use of vegetation types by radiomarked bobwhite (n = 30 coveys) and hunting dogs (n = 241) equipped with Global Positioning System collars during the 2014–2015 quail hunting season on Peabody Wildlife Management Area in western Kentucky. We surveyed hunting parties (n = 252) immediately after their hunt to determine success (flushed bobwhite) and gather hunt-party characteristics. We used associated habitat metrics from the dog track, weather variables, hunter and dog characteristics (e.g., age, experience), and hunt metrics (e.g., hours hunted, no. of dogs) to determine factors that influenced hunt success. Dogs used winter wheat firebreaks more than bobwhite regardless of time of day, forested areas more than bobwhite in the morning (0700–1000 hr) and midday (1000–1300 hr), disked areas more than bobwhite during midday, and open herbaceous areas less than bobwhite during morning and midday. The probability of success was positively influenced by number of dogs and hours hunted and negatively influenced by proportion of the hunt track in disked areas. Also, hunter success was greater in November compared with December and January. Our results indicated some key features associated with bobwhite habitat (open areas) may be underexploited by hunters, whereas other features (disked areas, firebreaks, and forested areas) may be overexploited. However, success was influenced primarily by factors that may be related to covey avoidance behavior resulting from substantial hunting pressure rather than where hunters selected to hunt. Lower bobwhite encounter rates (coveys flushed/hour) could cause hunter support to wane and bias hunting data as an indicator of population abundance.
Keywords: colinus virginianus; northern bobwhite; hunter success; Kentucky; hunting